Bioinformatic analysis confirms differences in circular RNA expression profiles of cumulus cells between patients with ovarian and peritoneal endometriosis-associated infertility - Huang, Xiaodi; Yu, Qi (Frontiers in Endocrinology, 2023)
Endometriosis has a detrimental effect on oocyte quality, and ovarian endometriosis (OEM) and peritoneal endometriosis (PEM) may have different effects on female fertility. Therefore, we conducted a study to explore the circular RNA (circRNA) expression profiles of cumulus cells (CCs) in patients with OEM (n = 3), PEM (n = 3), and tubal factor infertility (TFI, n = 3) using high-throughput sequencing techniques and attempted to identify common and unique circRNAs in the OEM and PEM groups. The CIRCexplorer2 program was used to identify circRNAs. Seven candidate circRNAs were validated in 30 samples using quantitative real-time polymerase chain reaction (qRT-PCR). Finally, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed to annotate the function of circRNA-targeted genes, which were verified by sequencing results and constructed circRNA–miRNA–mRNA networks. A total of 11833 circRNAs were identified in nine samples. The numbers of differentially expressed circRNAs between the OEM and TFI groups, PEM and TFI groups, and OEM and PEM groups were 130, 71, and 191, respectively. After taking intersections, 11 circRNAs were considered common circRNAs in the OEM and PEM groups; 39 circRNAs in the OEM group and 17 circRNAs in the PEM group were identified as unique key circRNAs. During qRT-PCR validation, hsa_circ_0003638 was significantly upregulated in the PEM group compared to that in the OEM and TFI groups. Functional analysis of circRNA-targeted genes revealed that apoptosis, PI3K-AKT, and p53 signaling pathways were enriched in the PEM–TFI comparison groups, whereas the functions of target genes involved in the JAK–STAT and TGF-β signaling pathways were enriched in the PEM–OEM comparison groups. Our findings confirmed differences in circRNA expression profiles of CCs between patients with OEM and PEM infertility and provide new insights into the different effects of various endometriosis phenotypes on oocytes.